Social media : a critical introduction - Fuchs, Christian (London Sage publ., 2021)
You will never look at social media the same way again. Social media are an integral part of contemporary society. From news and politics to language and everyday life, they have changed the way we communicate, use information and understand the world. So we have to ask critical questions about social media. We have to dig deeper into issues of ownership, power, class and (in)justice. This book equips you with a critical understanding of the complexities and contradictions at the heart of social media's relationship with society. The revised and expanded Third Edition: Explores populism, racism and nationalism in a new chapter on right-wing authoritarianism. Introduces the phenomenon of social media influencers in the age of Instagram, YouTube, and Snapchat. Explains how big data is central to social media in a new chapter on big data capitalism and imperialism. Explores the growing prominence of platforms and platform capitalism. Challenges you to envision and achieve a truly social media that serves the purposes of a just and fair world. Analyses fake news and misinformation in the context of Facebook and Cambridge Analytica. There are winners and losers in the age of digital capitalism. This book is an essential guide for anyone who wants to critically understand how we got to digital capitalism, and what we can do about it. Christian Fuchs is Professor of Media and Communication Studies and Director of the Communication and Media Research Institute (CAMRI) at the University of Westminster. --
What is a critical introduction to social media? -- What are social media? -- Big data capitalism -- The power and political economy of social media -- Google: good or evil search engine? -- Facebook and WhatsApp: surveillance in the age of fake news -- Influencer capitalism: reified consciousness in the age of Instagram, YouTube, and Snapchat -- Twitter and democracy: a new public sphere? -- Right-wing authoritarianism on social media -- Weibo: power, ideology, and social struggles in China -- The sharing economy of Airbnb, Uber, and Upwork -- Platform economy -- Wikipedia: a new democratic form of collaborative work and production? -- Capitalist social media's major problems and alternatives -- A manifesto for truly social media.
Previous edition: 2017.
Includes bibliographical references (pages 387-411) and index.
Keywords: Social media; Social media; Audiovisual aids; Mass media; Audiovisual aids; Comunication; Mass media; Social; Communication; Social